MANAJEMEN STRATEGI DALAM MENGGUNAKAN ANALISIS SWOT PADA RUMAH MAKAN TALAGO BIRU - Atika Fitriani; Rama Gita Suci; Cindy Fredicia Putri; Putri Dasti S Harahap (Komunitas Manajemen Kompetitif, 2025)
This study aims to develop an effective marketing strategy for Talago Biru Restaurant in Pekanbaru using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The research method used is descriptive with a qualitative approach. Data were collected through semi- structured interviews with the use of interview guidelines as the main tool for collecting information. The results of the analysis show that Talago Biru Restaurant has strengths in food quality and strategic location, but also faces challenges in the form of lack of digital promotion and high competition. The resulting strategies include four approaches: (1) S-O strategy (maximizing strengths to take advantage of opportunities) such as social media promotion and special menu diversification, (2) W-O strategy (improving weaknesses by using opportunities) such as adoption of digital payment technology and registration on online delivery platforms, (3) S-T strategy (utilizing strengths to face threats) such as savings packages and increased branding, and (4) W-T strategy (reducing weaknesses and avoiding threats) such as collaboration with local influencers. This study provides insight into the importance of adapting marketing strategies for MSMEs in facing the dynamics of business competition.